NCOG-45. DIFFERENTIAL AND DOSE-DEPENDENT EFFECTS OF CRANIAL IRRADIATION ON BRAIN STRUCTURES AND NEUROPSYCHOLOGICAL OUTCOMES IN CHILDREN WITH POSTERIOR FOSSA BRAIN TUMORS TREATED WITH DIFFERENT MODALITIES. (14th November 2022) - Dhanani, Sofia; O'Neil, Sharon; Cho, Scarlet; Shin, Brandon; Nelson, Marvin; Wong, Kenneth; Olch, Arthur; Tanedo, Jeffrey; Biele, Oliver; Lepore, Natasha; Nelson, Mary
Abstract: BACKGROUND: Studies investigating dose-dependent effects of cranial irradiation (CRT) in children with posterior fossa brain tumors are limited by examining combined effects of surgery, chemotherapy, and radiation. We aimed to determine alterations in brain volume and microstructure, and neuropsychological outcomes in children with posterior fossa tumors treated with surgery alone, surgery and chemotherapy, and surgery, chemotherapy, and CRT combined. We explored the relationship of radiation dose to the thalamus, putamen, and hippocampus to outcomes of intelligence, processing speed, executive functions, memory, and social/emotional functioning. METHODS: Forty-seven children with treated posterior fossa tumors (17 with surgery; 11 with surgery and chemotherapy; 19 with surgery, chemotherapy, and CRT) underwent neuroimaging and neuropsychological assessment a mean of 4.8 years after treatment, along with 17 healthy sibling controls (n=64). The putamen, thalamus and hippocampus were manually segmented on MRI, and structural mean radiation doses were calculated. Differences in demographics and medical history were evaluated using χ2 and t-tests. Linear regression examined differences in neuropsychological performance, structural volumes, and diffusion indices. Pearson correlation explored relationships of structural radiation doses to diffusion indices and neuropsychological outcomes. RESULTS: All patients scored lower on Block Design than controls (p=0.01), and the surgery and chemotherapy group scored the lowest. There was no significant difference in mean fractional anisotropy (FA) values in the thalamus, hippocampus and putamen between the three patient groups and controls. Hippocampal volume and mean radiation dose approached significant correlation (r= -0.49; p=0.07). Right putamen FA correlated with mean radiation dose (r=0.56; p=0.02). When controlling for age, thalamic volume was lowest in the irradiated group (p=0.02). CONCLUSIONS: Treatment of pediatric posterior fossa brain tumors with surgery, chemotherapy, and CRT impacts thalamic volume and may have a dose-dependent effect on the microstructure of the putamen compared to treatment with surgery/chemotherapy.